2003
DOI: 10.1021/la0341759
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Acidic Amphiphiles into Inverted Hexagonal Phases Using an l-Alanine-Based Surfactant as a Structure-Directing Agent

Abstract: Several taper-shaped, Brønsted acidic amphiphiles containing an amide linkage near the headgroup were synthesized with the goal of generating acidic, inverted hexagonal (HII) lyotropic liquid crystal (LLC) phases that can be stabilized by polymerization. These polymerizable acidic amphiphiles were synthesized by reacting the acyl chloride of 3,4,5-tris(11‘-acryloxyundecyloxy)benzoic acid with several amino acids (l-alanine, β-alanine, l-phenylalanine) and 2-aminoethanesulfonic acid. Of these derivatives, only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…4a) was designed and synthesized. [38] Monomer 1 was chosen as the starting point for a sulfonic acid derivative because 1 contains acrylate groups which are not susceptible to acid-catalyzed cationic polymerization, as opposed to the styryl groups on 2 and 3. [39] Unfortunately, it was found that 4 does not form a well-defined H II with water or dimethyl formamide (DMF), but rather a mixture of L and H II phases (Fig.…”
Section: Hydrogen-bond Templating Of Catalytic Amphiphiles Into Llc Pmentioning
confidence: 99%
See 3 more Smart Citations
“…4a) was designed and synthesized. [38] Monomer 1 was chosen as the starting point for a sulfonic acid derivative because 1 contains acrylate groups which are not susceptible to acid-catalyzed cationic polymerization, as opposed to the styryl groups on 2 and 3. [39] Unfortunately, it was found that 4 does not form a well-defined H II with water or dimethyl formamide (DMF), but rather a mixture of L and H II phases (Fig.…”
Section: Hydrogen-bond Templating Of Catalytic Amphiphiles Into Llc Pmentioning
confidence: 99%
“…4a). [38] We rationalized that extensive hydrogen bonding (H-bonding) of the sulfonic acid headgroup with surrounding water molecules increases the effective size of the hydrophilic headgroup, thereby perturbing the taper shape needed to form H II phases. Alternatively, the presence of the unsubstituted flexible ethyl tether may also have been detrimental to forming the desired taper shape required for H IIphase formation.…”
Section: Hydrogen-bond Templating Of Catalytic Amphiphiles Into Llc Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Interesting study on aggregation properties of amino acid amphiphiles has been reported by Huang and co-workers [9]. Acidic amphiphiles based on L-alanine surfactant with specific structuredirecting properties have been explored by Gin and co-workers [10]. New materials such as gel emulsions from these amphiphiles for specific applications have been achieved [11].…”
Section: Introductionmentioning
confidence: 99%